Credit Card Applications Pending – Who are Our Best Prospect Cardholders? Improved Decisions through Business Analytics and Business Intelligence. Issue 1 (May 2018) - Chongwatpol, Jongsawas
This case is designed to illustrate how to utilize the business intelligence framework and business analytics to make proper decisions in the turbulent and competitive business environment. The case started when Jong, the junior vice president in the modeling and analyst department of ABC Bank of Thailand, and his team were drafting a proposal presentation on the new credit card approval processes. Jong believed that it was time to overhaul credit card application processes by employing more sophisticated analytical techniques to analyze customer and credit card data. ABC - Premier Card, the bank's most popular card offering, would be a serendipitous test case in which to further develop the idea about improvements in approving credit card applications. Currently, there were 5 ABC - Premier card applications pending for decision in the house file. Tightening the credit approval process was one of the important strategies for the bank to potentially avoid an increase of risky customers. However, overly strict declinations of credit card applications might alienate potential customers and causing the bank to forego profitable lending opportunities. Taking the ABC - Premier card applications as a testing scenario, Jong and his team had to come up with a new method to evaluate each credit card applicant. They could approve all of them instantly, approve some of them, or even decline all of them. Consequently, Jong hoped that this proposed credit card approval method would improve the bank's policy decision to optimally balance both risky and profitable customers in the long run.